MENGENAL LEBIH DALAM PERKEMBANGAN BAHASA, EKSPRESI, DAN RESEPTIF PADA ANAK USIA DINI: GETTING TO KNOW MORE ABOUT LANGUAGE, EXPRESSION, AND RECEPTIVE DEVELOPMENT IN EARLY CHILDHOOD - Munawaroh, Hidayatu; Septiyaningrum, Dina Rus; Zahra, Firza Hardyn Aira (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
This article discusses getting to know more deeply about language development, Expression and Receptivity in Early Childhood in learning, development of skills, as well as children’s expertise in understanding and applying new words. This article aims to train and find the impact of implementing children’s learning in early childhood language aspects. The development of language or communication in children is one aspect of a child’s developmental stages that should not escape he attention of educators in general and parents in particular. The acquisition of language by children is the greatest and most amazing human achievement. During early childhood, namely from birth to 6 years of age, he never learned language, let alone specific vocabulary, ut by the end of his early childhood, the average child had stores more than 14.000 vocabulary words. The stages of language development are as follow: 1) stage I (Pre-linguistic). 2) Stage II (Linguistic). 3) stage III (grammar development). 4) Stage IV ( grammar). Aspects of children’s language development consist of: 1)Vocabulary, 2) Syntax (grammar), 3) Semantics.